The PINK1 repertoire: Not just a one trick pony. (7th October 2021) - Pollock, Liam; Jardine, Jane; Urbé, Sylvie; Clague, Michael J.
Abstract: PTEN‐induced kinase 1 (PINK1) is a Parkinson's disease gene that acts as a sensor for mitochondrial damage. Its best understood role involves phosphorylating ubiquitin and the E3 ligase Parkin (PRKN) to trigger a ubiquitylation cascade that results in selective clearance of damaged mitochondria through mitophagy. Here we focus on other physiological roles of PINK1. Some of these also lie upstream of Parkin but others represent autonomous functions, for which alternative substrates have been identified. We argue that PINK1 orchestrates a multi‐arm response to mitochondrial damage that impacts on mitochondrial architecture and biogenesis, calcium handling, transcription and translation. We further discuss a role for PINK1 in immune signalling co‐ordinated at mitochondria and consider the significance of a freely diffusible cleavage product, that is constitutively generated and degraded under basal conditions. Abstract : The Parkinson's disease‐related protein PINK1 has a well‐established role in promoting mitophagy of damaged mitochondria. Here, Pollock et al . highlight a broader landscape of PINK1‐associated cell physiology. This includes other key aspects of mitochondrial homeostasis and damage sensing, as well as immune and calcium signalling.